2021
DOI: 10.1016/j.hroo.2021.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of dantrolene in doxorubicin-induced cardiomyopathy in mice

Abstract: BACKGROUND Doxorubicin (Dox) is a potent chemotherapeutic agent, but its usage is limited by dose-dependent cardiotoxicity. Intracellular calcium dysregulation has been reported to be involved in doxorubicin-induced cardiomyopathy (DICM). The cardioprotective role of RyR stabilizer dantrolene (Dan) on the calcium dynamics of DICM has not yet been explored. OBJECTIVE To evaluate the effects of dantrolene on intracellular calcium dysregulation and cardiac contractile function in a DICM model.METHODS Adult male C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Therefore, our manuscript focused on the effect of Rhy on sarcoplasmic reticulum calcium release. According to existing literature reports, DTL is a stabilizer of RyR2 that could protect cardiomyocytes by regulating intracellular calcium homeostasis ( Azam et al, 2021 ). Therefore, this chemical was chosen as a positive control drug in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our manuscript focused on the effect of Rhy on sarcoplasmic reticulum calcium release. According to existing literature reports, DTL is a stabilizer of RyR2 that could protect cardiomyocytes by regulating intracellular calcium homeostasis ( Azam et al, 2021 ). Therefore, this chemical was chosen as a positive control drug in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the failure of antioxidants, β-blockers and iron chelation therapies in treating DICM, a targetable mechanism underlying DICM has yet to found. Interestingly, abnormalities in the regulation of intracellular calcium (Ca 2+ ) cycling is commonly observed in the development of cardiomyopathy, in addition to exposure to doxorubicin [6][7][8][9] .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Interestingly, abnormalities in the regulation of intracellular calcium (Ca 2+ ) cycling are commonly observed in the development of cardiomyopathy, which is also often accompanied by exposure to Dox. 6 , 7 , 8 , 9 …”
mentioning
confidence: 99%
“…An alternative approach would be to reduce RyR2 leak with RyR2 inhibitors, which could be a promising new therapeutic strategy against lethal arrhythmias and HF. Recent studies have shown the positive effects of the RyR2 inhibitor dantrolene on atrial fibrillation inducibility in animal models of myocardial infarction [22][23][24][25] . However, the utility of chronic inhibition of RyR2 in non-ischemic heart failure has not been studied.…”
Section: Introductionmentioning
confidence: 99%